PERTIMBANGAN HUKUM PUTUSAN HAKIM MILITER BERBASIS ASAS, TEORI DAN DOKMATIK HUKUM (Lex Jurnalica, 2019)
AbstractIn carrying out its juridical duties a judge is bound by a principle called the Ius Curia Novit principle, which means that the judge is deemed to have to know the law in each case he is handling. However, when the judges want to apply and use the laws and regulations on the cases they handle it turns out that the regulation in question does not exist or there is a legal vacuum, then what the judge needs to do is